Tinjauan Yuridis Terhadap Perceraian Bagi Pegawai Negeri Sipil - I Made Gede Adi Palguna (Jurnal Ilmiah Raad Kertha, 2019)
Marriage is a bond the inner and outer man and woman as husband and wife with the aim offorming a family or household that is happy and eternal based on one supreme divinity. Divorce is theelemination of the marriage with the decision of the judge or the demands of one of the parties to themarriage.Civil servants who will do the divorce or certificate in advance of the official. Issues raisedin this research is how the procedure to be followed for civil servants to obtain a permit divorce andhow the legal consequences arising from divorce for civil servants. This study is the legal normative,conceptual approach and approach the laws. Legal materials used are the primary legal material andsecondary legal materials. Collection of legal material is done by quoting, summarizing and providesreviews and documentation of primary legal materials. Analysis of legal material used are collectinglegal material which is then analyzed systematically. Procedure to be followed in obtaining permitsdivorce for civil servants is a must have permission from his superiors to those in change of civilservants. Environment, respectively the first to be attempted reconciliation between the husband andwife, if not succesful, then the officer tok the decision at the request of the divorce license with considerthe reason the reason. Legal consequences arising from divorce to civil servants is due to the law of thehusband and wife are legal consequences for children are sharing custody of children as a result ofmarital property, namely the division of joint property or possessions together.